Criminal Law Enforcement Against E-Commerce Fraud: A Case Study of East Java Regional Police - Jessyca Dea elhelmindo Bua Hetady; Dr. Jonaedi Efendi S.Hi.,M.H (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
This study aims to examine the efforts and challenges faced by the East Java Regional Police in enforcing the law against e-commerce fraud, which has become increasingly prevalent in the digital era. The research employs a qualitative method with a juridical-empirical approach and a descriptive research type, by collecting primary data through direct interviews with the Head of the Cyber Unit at the East Java Regional Police and victims of fraud, as well as secondary data from legislation such as the Indonesian Penal Code (KUHP) and Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law), supplemented by secondary and tertiary legal materials from various relevant literature and sources. The data analysis was conducted using triangulation by combining various data sources to enhance the validity of the findings. The results show that the East Java Police have made systematic efforts to enforce the law on e-commerce fraud, including digital data analysis, cyber forensic involvement, and coordination with financial authorities such as OJK and Bank Indonesia. However, the effectiveness of these efforts is hindered by technological limitations, a lack of skilled human resources, low digital literacy among the public, and suboptimal regulatory support and collaboration with e-commerce platforms. Therefore, strengthening institutional capacity and inter-agency synergy is essential to address the growing challenges of digital crime.